Maize Vegetative Growth Response to Poultry Manure and Sowing Date during Delayed onset of Rainfall in a Humid Agroecology of Nigeria (Global Journal of Science Frontier Research, 2021)
Soil moisture deficit due to delayed onset of rainfall creates stress conditions at the early season when maize is at the early vegetative stage of growth. In 2009 and 2010 the impact of poultry manure and sowing date on maize vegetative growth during delayed onset of rainfall was assessed in a rainforest agroecology of Nigeria. The treatments comprised four sowing dates (February 28, March 15, March 30 and April 14), three maize varieties (TZE COMP3C3, TZL COMP4C3 and OKA AWAKA) and two poultry manure rates (0 and 10 tons ha-1). These treatments were arranged as a split-split plot and laid out in randomized complete block design with three replications. Maize vegetative parameters, including height, number of leaves, leaf area and stem dry weight were significantly affected by year of cropping, thereby indicating inter-annual variability in climatic variables.
Keywords: delayed onset; maize; moisture deficit; poultry manure; rainfall; sowing date